2020
DOI: 10.1111/trf.15652
|View full text |Cite
|
Sign up to set email alerts
|

Field‐expedient thawing of fresh‐frozen plasma

Abstract: INTRODUCTION Frozen plasma is superior to crystalloids for hemorrhage resuscitation but remains logistically challenging in austere environments because of specialized clinical equipment for on‐demand thawing. This research examines some ad hoc thawing techniques that have been implemented by military medical personnel. METHODS Fresh‐frozen plasma (FFP) units were thawed accordingly: using a slow cooker (three temperature settings) with preheated or room temperature water; affixing flameless ration heaters fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several studies have now shown that management of major bleeding associated with trauma with early plasma transfusion, for both hospital and pre‐hospital care, improves survival 1 and reduces death due to exsanguination 2 . Most countries use fresh frozen plasma (FFP) components to resuscitate bleeding patients in emergencies, however, one of the main limitations of frozen products is the need for thawing, which can take between 20 and 30 min depending on the thawing devices used 3‐6 . Being able to store thawed FFP for extended periods at 2° to 6°C is one way to improve the availability of plasma in emergency settings, and some countries have already implemented this practice by extending the shelf life of thawed plasma for up to 120 h 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have now shown that management of major bleeding associated with trauma with early plasma transfusion, for both hospital and pre‐hospital care, improves survival 1 and reduces death due to exsanguination 2 . Most countries use fresh frozen plasma (FFP) components to resuscitate bleeding patients in emergencies, however, one of the main limitations of frozen products is the need for thawing, which can take between 20 and 30 min depending on the thawing devices used 3‐6 . Being able to store thawed FFP for extended periods at 2° to 6°C is one way to improve the availability of plasma in emergency settings, and some countries have already implemented this practice by extending the shelf life of thawed plasma for up to 120 h 7,8 .…”
Section: Introductionmentioning
confidence: 99%